Interference of Eupatorium adenophorum (Spr.) and its allelopathic effect on growth and yield attributes of traditional food crops in Indian Himalayan Region. Issue 5 (21st August 2019) - Rawat, Lakhpat S.; Maikhuri, Rakesh K.; Bahuguna, Yateesh M.; Maletha, Ajay; Phondani, Prakash C.; Jha, Nabi K.; Pharswan, Dalbeer S.
Abstract: The objective of this study was to understanding the allelopathic dynamic of invasive species Eupatorium adenophorum residues against traditional crops viz., Amaranthus caudatus and Vigna unguiculata in laboratory and green house. In laboratory, the effect of different concentrations of the aqueous extract and leaf leachate of decomposed residues (DR) and un‐decomposed residues (UDR) of the selected weed was examined on shoot and root length of the selected crops. In pot study, different concentrations of dose and leachate of DR and UDR of selected weed was evaluated against growth and yield performance of the studied crops. Shoot and root length of both crops was significantly reduced by the aqueous extract of both kinds of residues. Aqueous extract at 8% of UDR residues was noticed to be harmful to V. unguiculata and reduced 66.23% and 75.28% shoot and root length, respectively. Similarly, soil amended with DR and UDR of the weed had a significant effect on growth and yield attributes of the studied crops and reduced 64.90% growth and 86.30% branch/plant of V. unguiculata at 8% concentration compared to control soil. A significant amount of water‐soluble phytotoxins was found in the UDR and DR of E. adenophorum . Leaf leachate of the selected weed was more harmful as compared to aqueous extract and soil amended residues. The UDR was found to be more phytotoxic than DR. These results suggest that the phytotoxic potential of E. adenophorum to plant community could be minimized if the whole plant of invasive weed is decomposed. Abstract : Allelopathic dynamics of the residues of invasive weed was assessed. The undecomposed residue was more inhibitory to test crops as compared to decomposed. The phytotoxic effect of residues of invasive weed could be reduced if decomposed.